A new, three-dimensional method for determining tooth wear. - Mayhall, John T.; Kageyama, Ikuo (American Journal of Physical Anthropology, 1997)
The writers outline a method that combines moiré contourography with digital image analysis to ascertain not only the reduction in cusp height but also the actual amount of tooth material lost through attrition and abrasion of molars. They contend that this method contributes a dynamic aspect to wear studies by outlining the amount of tooth substance lost over a period of time. In addition, they point out that the method can be employed alone or in conjunction with the depth gauge methods proposed by Tomenchuk and Mayhall, Molnar, and colleagues to help determine the age of individuals in a population where some can be accurately aged but others cannot. Finally, they point out situations where the moiré method is not recommended for use.